Gratitude as a Psychotherapeutic Intervention. Issue 8 (17th June 2013) - Emmons, Robert A.; Stern, Robin
<x xml:space="preserve">Abstract</x> Gratitude practice can be a catalyzing and relational healing force, often untapped in clinical practice. In this article, we provide an overview of current thinking about gratitude's defining and beneficial properties, followed by a brief review of the research on mental health outcomes that result from gratitude practice. Following an analysis of our case study of the use of gratitude as a psychotherapeutic intervention, we present various self‐strategies and techniques for consciously choosing and cultivating gratitude. We conclude by describing ways in which gratitude might be capitalized upon for beneficial outcomes in therapeutic settings.